Use of magnetic resonance imaging in the diagnosis of temporomandibular dysfunction: an integrative review - Karolayne Dutra Felix,; Victoria Alice Menezes Gomes,; Maria Lúcia Ribeiro Barbosa,; Katia Caetana Pereira,; João Victor Monteiro Moura,; Letícia Kelly Cabral de Pontes,; Thaís Nicolle Brilhante Sousa,; Elizabety do Nascimento Silva,; Maria Eduarda Batista Henriques,; Livia Silva Galiza,; Maria Paula Melo Coutinho,; Arthur Felipe de Brito Andrade,; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Temporomandibular dysfunction (TMD) involves a variety of conditions that affect the temporomandibular joint (TMJ) and associated structures, generating symptoms such as pain, limited movement and joint noise. Given the anatomical complexity of the TMJ and the diversity of symptoms, accurate diagnosis is challenging. Magnetic resonance imaging (MRI) stands out as an effective test for assessing soft tissues, such as the articular disc, and can detect disc displacements, joint effusion and inflammation. Aim: This study aims to assess whether MRI is the most appropriate test for diagnosing temporomandibular disorders, taking into account divergent opinions among specialists and the scientific literature. Materials and Methods: An integrative literature review was carried out using PubMed, Scopus and Web of Science databases, as well as Google Scholar for gray literature. Controlled descriptors were used, combined with Boolean operators. Results and Discussion: Although MRI is effective for assessing soft tissues and disc displacements, it has limitations in detecting bone abnormalities, which can compromise a comprehensive diagnosis. Therefore, the combination of other imaging techniques is recommended for a complete evaluation. Conclusion: MRI is an important tool, but not sufficient on its own. The complementary use of other diagnostic modalities is essential for an accurate diagnosis of TMD.